THE EFFECT OF POLYSILAZANE ON THE DENSIFICATION AND MECHANICAL PROPERTIES OF SICF/SIC COMPOSITES - Alfian Noviyanto (SINERGI, 2020)
The effect of polysilazane on the densification and mechanical properties of SiCf/SiC composites was examined thoroughly. The polysilazane was infiltrated into the fiber area, followed by pyrolysis at 1450°C for 4 h in an argon atmosphere. Furthermore, the SiC fabrics contain the pyrolyzed polysilazane was infiltrated by β-SiC slurry and sintered at 1750°C for 2 h in an argon atmosphere. The density of SiCf/SiC composites with and without the addition of polysilazane was 2.65 and 3.05 g/cm3, respectively. The pores in the fiber area were observed for the SiCf/SiC composites with the addition of polysilazane. However, the fine-grained size in the matrix area was obtained by the addition of polysilazane. The average grain size of the SiCf/SiC composite with and without the addition of polysilazane was 253 and 740 nm, respectively. Indeed, the hardness of the matrix area for SiCf/SiC composites with the addition of polysilazane (31.6 ± 1.8 GPa) was higher compared to SiCf/SiC composites without polysilazane (27.4 ± 1.6 GPa).